2023
DOI: 10.3390/sports11010011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Frequency with Complex Contrast Training on Measures of Physical Fitness in Active Adult Males

Abstract: Complex contrast training (CCT) is an exercise modality that utilizes both high-load resistance activity and low-load plyometric activity in a set-by-set fashion within a single exercise session. Such a combination of exercises targets multiple aspects of the force–velocity curve and may thus lead to improvement of various components of physical fitness. However, no previous study has attempted to compare the effects of load-equated two vs. three CCT sessions per week on measures of physical fitness. Forty-fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Demographic data were collected and 1RM tests were performed during these familiarization sessions. The 1RM assessments were conducted according to methods outlined in a previous study [24] to define the load prescription for each participant during the high-load activities (i.e., squat, lunges, Romanian deadlift, bench press). The 1RM obtained for squat, lunges, Romanian deadlift, and bench press were 107 ± 10 kg, 64 ± 8 kg, 91 ± 11 kg, and 69 ± 10 kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographic data were collected and 1RM tests were performed during these familiarization sessions. The 1RM assessments were conducted according to methods outlined in a previous study [24] to define the load prescription for each participant during the high-load activities (i.e., squat, lunges, Romanian deadlift, bench press). The 1RM obtained for squat, lunges, Romanian deadlift, and bench press were 107 ± 10 kg, 64 ± 8 kg, 91 ± 11 kg, and 69 ± 10 kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…J. Sport Tourism 2023, 30(3), [29][30][31][32][33][34][35] strength and conditioning coaches in overcoming congested weekly micro-cycles [11,23,24].…”
Section: Original Research Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDT group completed the RT exercise sets first followed by plyometric exercise sets. The exercises were selected based on a previous study on complex training [24]. The first two weeks constituted the anatomical adaptation phase and hence an intensity of 65% 1RM to induce the initial neural adaptations.…”
Section: Training Interventionmentioning
confidence: 99%
“…Furthermore, CCT has been extensively investigated with regard to training variables ( Cormier et al, 2020 ); however, training frequency remains an important variable that requires further study. Recently, Kumar et al (2023) showed that CCT with a different weekly frequency (2 vs . 3 training sessions per week) and equalized volume load had similar effects on measures of physical fitness in active adult males.…”
Section: Introductionmentioning
confidence: 99%